Occupational Noise Exposure And Hearing Loss Prevalence Among The Grass Cutters Of USM, Penang - Ahmad, Mohammad Zaip (2012)
Exposure to excessive noise can cause many adverse health effects including hearing loss. Even though hearing loss from noise exposure has been recognized since the industrial revolution and the noise legislations in the work place has been enacted over the last two decades, but it remains as one of the most prevalent occupational health problems in many countries of the world. In Malaysia, little is known about noise exposure and hearing loss among grass cutters who operate the back pack grass cutting machine. The main purpose of this study is to determine the level of noise exposure from the grass cutting machine and the prevalence of hearing loss among the workforce of USM grass cutters.